South Africa's freight transport involvement options in Sub-Saharan Africa : declining infrastructure and regulatory constraints - De Bod, Anneke (Stellenbosch : Stellenbosch University, 2008)
Thesis (MComm (Logistics))--Stellenbosch University, 2008.